2003
DOI: 10.1002/ajmg.a.20283
|View full text |Cite
|
Sign up to set email alerts
|

A genome‐wide scan for loci predisposing to non‐syndromic cleft lip with or without cleft palate in two large Syrian families

Abstract: Non-syndromic cleft lip with/without cleft palate (CL/P) is a common, usually non-fatal birth defect of complex etiology. Several segregation analyses have demonstrated that genetic factors are important in the pathogenesis of CL/P, most likely through the interaction of several genes of modest effects. The aim of this study was to perform a genome-wide linkage analysis to identify/search for candidate gene loci for CL/P. We conducted a genome-wide search in two large, relatively isolated Syrian families, each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 78 publications
3
36
0
2
Order By: Relevance
“…This region was first identified by Prescott et al in a genome scan of Caucasian NSCLP sib pairs, and subsequently in four other genome scans of different NSCLP populations (19,21,25,26,28). Analysis of STR D16S3037 in our dataset provided evidence for an association with NSCLP (P = 0.00063).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…This region was first identified by Prescott et al in a genome scan of Caucasian NSCLP sib pairs, and subsequently in four other genome scans of different NSCLP populations (19,21,25,26,28). Analysis of STR D16S3037 in our dataset provided evidence for an association with NSCLP (P = 0.00063).…”
Section: Discussionsupporting
confidence: 60%
“…Linkage disequilibrium (LD) analysis identified STR marker D16S3037, in the 16q24.1 chromosomal region, that was significantly associated with NSCLP (P = 0.00063). Results from three other NSCLP genome scans and one targeted genome scan have also suggested that a NSCLP candidate gene lies on the long arm of chromosome 16, between 16q21-24, which includes D16S3037 (19,21,25,28).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first CL/P scan was performed on 92 British sibpairs and identified a total of nine regions with suggestive results [49]. This has been followed by five additional scans of varying size (Table 2) [20,24,[49][50][51][52][53][54]. In general, the results have been modest with the exception of a log odds ratio (LOD) score of 3.0 at 17p13.1 in a scan of two large Syrian families [50].…”
Section: Genome Scans Identify Novel Locimentioning
confidence: 99%
“…This has been followed by five additional scans of varying size (Table 2) [20,24,[49][50][51][52][53][54]. In general, the results have been modest with the exception of a log odds ratio (LOD) score of 3.0 at 17p13.1 in a scan of two large Syrian families [50]. The most consistent loci are 2p13 (TGFA), 2q35-q37, 3p21-p24, 4q32-q33, 6p23-p25, 9q22-q33, 14q12-q31, and 18q11-q12, with the remaining 23 loci being unique to the population studied.…”
Section: Genome Scans Identify Novel Locimentioning
confidence: 99%